Profiling the natural settlement habitat of spiny lobster, Panulirus spp. to determine potential diets and rearing conditions in a lobster hatchery (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Amin M, Harlyan LI, Achmad K, Diantari R. 2022. Profiling the natural settlement habitat of spiny lobster, Panulirus spp. to determine potential diets and rearing conditions in a lobster hatchery. Biodiversitas 23: 2893-2898. The high demand for spiny lobster seeds has triggered research on seed production in a hatchery system. However, the remaining challenges are still in determining suitable live diets and environmental conditions at the early life stages. Thus, the present study investigated the natural settlement habitat of lobster larvae as basic information for developing diets and rearing conditions in an indoor system. One of the most common natural settlement habitats for lobster larvae in Indonesia, indicated by the high catching rates, Gerupuk Bay located in West-Nusa Tenggara, was selected as a studied area. Physicochemical and biological parameters were investigated to obtain the habitat profiles. The results showed that Gerupuk Bay was 18-30 m water depth, 5-6 m transparency, a sandy, and rocky bottom, 27-31oC temperature, 0.1-0.2 m.s-1 current, 5-6 mg/L dissolved oxygen,
Keywords: Ecology, natural habitat, post-larval stage, recruitm